Pengaruh Personality Behavior dalam Komunikasi Mahasiswa Inhil terhadap Budaya Jawa: Pendekatan Integrasi Theory of Planned Behavior (TPB) - Sulaiman Abdul Rasid (Universitas Islam Indragiri, 2025)
This study explores the impact of personality traits on the socio-cultural adaptation of Indragiri Hilir students in Ponorogo, using the Big Five Personality Traits and the Theory of Planned Behavior (TPB). Data were analyzed with PLS-SEM. Neuroticism has the strongest influence on Attitude Towards Behavior (ƒ² = 0.648), while other traits have minor effects. ATB (ƒ² = 0.205) and Subjective Norms (ƒ² = 0.210) moderately affect socio-cultural behavior changes. The model shows strong predictive ability for ATB (R² = 0.856), moderate for CSB (R² = 0.595), and small for SN (R² = 0.487). The findings emphasize the role of personality in adaptation and recommend cultural exchange programs for student organizations.